2008
DOI: 10.1007/s12022-008-9029-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features of Growth Hormone-producing Pituitary Adenomas: Difference among Various Types Defined by Cytokeratin Distribution Pattern Including a Transitional Form

Abstract: Pituitary adenomas producing almost exclusively growth hormones (GH) have been ultrastructurally classified into two distinct types: densely granulated somatotroph (DG) adenomas and sparsely granulated (SG) adenomas. Fibrous body (FB), an intracytoplasmic globular aggregation of cytokeratin (CK) filaments, is a hallmark of SG adenomas. Under light microscope, FB could be identified by CK immunohistochemistry as a dot-pattern immunoreaction versus a perinuclear pattern for cells without FB. However, it has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
120
5
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(157 citation statements)
references
References 13 publications
22
120
5
10
Order By: Relevance
“…This finding coincides with the report of Mazal et al (11) and Obari et al (9). With respect to the tumour size, our findings were similar to the findings reported by Mazal et al (11) who also observed that DP adenomae were significantly larger than non-DP adenomae.…”
Section: Ck Staining Patterns and Clinico-pathological Featuressupporting
confidence: 93%
See 2 more Smart Citations
“…This finding coincides with the report of Mazal et al (11) and Obari et al (9). With respect to the tumour size, our findings were similar to the findings reported by Mazal et al (11) who also observed that DP adenomae were significantly larger than non-DP adenomae.…”
Section: Ck Staining Patterns and Clinico-pathological Featuressupporting
confidence: 93%
“…Other factors influencing tumour growth, such as apoptotic process, cell-cell junction and intercellular communication, should be further investigated to understand the linking mechanisms between CK expression and tumour growth. DP adenomae did not have the tendency to be more invasive than the other types; a finding that is inconsistent with the reports by Mazal et al (11) and Obari et al (9), where both groups determined invasion by Knosp grading (26). However, we evaluated the invasion into cavernous sinus based on intraoperative findings under microscopic and/or endoscopic observations in addition to preoperative MRI findings.…”
Section: Ck Staining Patterns and Clinico-pathological Featurescontrasting
confidence: 62%
See 1 more Smart Citation
“…[3][4] As a consequence, differentiated adenomas usually exhibit diffuse adenohypophysial hormone positivity, with the exception of sparsely granulated somatotroph adenomas where positivity for GH can be focal and weak, however, the presence of fibrous bodies in 475% of tumor cells is identified. [3][4][5]22 In contrast to differentiated Pit-1 cell lineage adenomas, silent subtype 3 adenomas show variable, focal or scattered positivity for one or more adenohypophysial hormones including GH, PRL and beta-TSH. These features are consistent with a monomorphous plurihormonal adenoma of Pit-1 lineage in the vast majority of our cases.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokeratin staining is used in clinical practice to characterise densely granulated adenomas having cytokertain staining with perinuclear pattern and sprasely granulated adenomas having dot-like pattern (Obari et al 2008). Sparsely granulated somatotrophinomas occur in younger patients, are larger and more invasive than densely granulated tumours and typically express SSTR5 but not SSTR2 (Mayr et al 2013), while densely granulated adenomas present higher levels of SSTR2 and are more responsive to SSA treatment (Obari et al 2008, Fougner et al 2012, Kato et al 2012, Brzana et al 2013, Larkin et al 2013.…”
Section: Granulation Patternmentioning
confidence: 99%